The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7567/jjap.55.05fj07
|View full text |Cite
|
Sign up to set email alerts
|

Realization of high-performance hetero-field-effect-transistor-type ultraviolet photosensors using p-type GaN comprising three-dimensional island crystals

Abstract: High-performance AlGaN/AlGaN hetero-field-effect-transistor (HFET)-type photosensors with high photosensitivity were fabricated using p-type GaN comprising three-dimensional island crystals. The p-type GaN layers were grown on AlGaN layers at a high AlN molar fraction, and the area of p-type GaN comprising three-dimensional island crystals increased as the thickness of the p-type GaN film decreased, resulting in a reduced p-type GaN coverage ratio. The p-type GaN layers comprising three-dimensional island crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…This phenomenon arises from optical gain. For AlGaN HEMTs, optical gain is attributed to generation of free holes in the barrier layer, thereby enhancing the 2D electron gas (2DEG) or collection of free carriers generated in the channel layer by the depletion region under the gate [142] . In addition, sub-bandgap absorption by either the barrier or the channel layer has also been observed to produce strong thresholds in photoresponse in AlGaN HEMTs, indicating that deep level defects can function in the photoresponse [143] .…”
Section: Phototransistormentioning
confidence: 99%
“…This phenomenon arises from optical gain. For AlGaN HEMTs, optical gain is attributed to generation of free holes in the barrier layer, thereby enhancing the 2D electron gas (2DEG) or collection of free carriers generated in the channel layer by the depletion region under the gate [142] . In addition, sub-bandgap absorption by either the barrier or the channel layer has also been observed to produce strong thresholds in photoresponse in AlGaN HEMTs, indicating that deep level defects can function in the photoresponse [143] .…”
Section: Phototransistormentioning
confidence: 99%
“…By using p-type GaN or Schottky electrode, it is possible to expect a low dark current by forming a depletion layer, resulting in high rejection ratio as a result. [27][28][29] We also reported the result of applying this device structure to photosensor with photosensitivity in visible light region. 25,26) In these reports, the photosensors with photosensitivity of 4 × 10 5 A W −1 at approximately 380 nm, rejection ratio of 17, and absorption wavelength edge of 450 nm were realized by using p-type GaInN gate.…”
mentioning
confidence: 95%
“…[15][16][17][18][19][20] Thus far, we have reported high photosensitivity AlGaN/GaN heterostructure field effect transistor (HFET) type photosensors with p-type GaN optical gate, AlGaN/GaN HFET type photosensor with p-type GaInN optical gate, AlGaN/AlGaN HFET type photosensor with p-type GaN optical gate, and AlGaN/ AlGaN HFET type photosensor with Schottky electrode gate, respectively. [21][22][23][24][25][26][27][28][29] Since these HFET type photosensors have two-dimensional electron gas (2DEG) with high mobility, a large gain is obtained and as a result high photosensitivity is realized. By using p-type GaN or Schottky electrode, it is possible to expect a low dark current by forming a depletion layer, resulting in high rejection ratio as a result.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18,19) Yamamoto et al reported the correlation between the film thickness and surface morphology in the growth of a p-GaN gate in an AlGaN/AlGaN heterostructure field effect transistor sensor using MOVPE. 20) Films of p-GaN with <50 nm thickness have low coverage because of the island growth at the initial stage of GaN growth. At a higher film thickness of ∼100 nm, the islands coalesce to form a flat GaN surface.…”
mentioning
confidence: 99%